DISHARMONI PERTANGGUNGJAWABAN PIDANA DISABILITAS MENTAL DALAM HUKUM POSITIF DI INDONESIA - Faiz Aqiel Maula Hidayat (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Criminal acts, which in essence cannot be separated from social life, seem to not only occur among ordinary people, but can also occur for and against persons with disabilities. However, the author sees that arrangements regarding criminal liability, especially for persons with disabilities, still contain ambiguity and disharmony between one another. So the authors in this paper aim to discuss the criminal responsibility of persons with mental disabilities in positive law in Indonesia, by using juridical-normative research methods and guided by the statutory and regulatory approach and case approach. The problems in this study were then analyzed and presented in the form of descriptive-qualitative research, so that the results of the research were that in Indonesia's current legal regulations regarding criminal acts by perpetrators of persons with disabilities there are no provisions governing the criminal liability of persons with disabilities at all. Thus, there is a disharmony in the laws and regulations regarding this matter which results in disparity in the judge's decision, even though it involves expert testimony as the judge's consideration. If using a futuristic interpretation that is in line with progressive legal theory, then the existence of the Law on Persons with Disabilities needs to be revised. This is also an implication of the birth of a new Criminal Code which in Articles 38 and 39 regulates more specifically in this regard compared to the old Criminal Code, but still requires further explanation and discussion in the Law on Persons with Disabilities. So in this case the author provides suggestions and recommendations in the form of the need for revision of the Law on Persons with Disabilities as a form of harmonization of positive law in Indonesia.